Causal links between Nile floods and eastern Mediterranean sapropel formation during the past 125 kyr confirmed by OSL and radiocarbon dating of Blue and White Nile sediments. (15th December 2015) - Williams, M.A.J.; Duller, G.A.T.; Williams, F.M.; Woodward, J.C.; Macklin, M.G.; El Tom, O.A.M.; Munro, R.N.; El Hajaz, Y.; Barrows, T.T.
Abstract: It has long been hypothesised that beds of highly organic mud or sapropels seen in marine sediment cores retrieved from the floor of the eastern Mediterranean accumulated during times of high Nile fluvial discharge. Our recent fieldwork in the valleys of the Blue Nile, the White Nile and the main Nile has for the first time revealed a sequence of extreme flood episodes synchronous with sapropel units S5 (124 kyr), S4 (102 kyr), S3 (81 kyr), S2 (55 kyr) and S1 (13.5–6.5 kyr). There are more weakly defined links with Nile floods and sapropel units S9 (240 kyr), S8 (217 kyr), S7 (195 kyr), S6 (172 kyr), but the dating error terms are too large to allow us to be too definite. During times of extreme floods over the past 125 kyr, wide distributary channels of the Blue Nile flowed across the Gezira alluvial fan in central Sudan and transported a bed load of sand and gravel into the lower White Nile valley. The sands were reworked by wind to form source-bordering dunes, all of which contain heavy minerals of Ethiopian provenance. These source-bordering dunes were active at 115–105 kyr, 60 kyr and 12–7 kyr, all times of extreme Blue Nile floods. The flood and dune sediments were dated using a combination of optically stimulated luminescence (OSL) and radiocarbon analyses. The Quaternary record of Nile floods discussed here shows a precessional signal and reflects episodes of stronger summer monsoon and more northerly seasonal movement of the ITCZ, linked to times of higher insolation in northern tropical latitudes. Progressive aggradation of Holocene Nile channels in northern Sudan has had a profound influence upon human settlement in the last 8 kyr. Highlights: The alluvial record from the Blue and White Nile valleys now spans the last 250 kyr. Episodes of extreme Nile flow coincide with sapropel units in the eastern Mediterranean. The Blue and White Nile responded differently to past changes in climate. Source-bordering dunes in the lower White Nile valley formed from Blue Nile sands.